Population Health, Prevention, Health Promotion, and Wellness Competencies in Physical Therapist Professional Education: Results of a Modified Delphi Study. Issue 9 (13th April 2020) - Magnusson, Dawn M; Rethorn, Zachary D; Bradford, Elissa H; Maxwell, Jessica; Ingman, Mary Sue; Davenport, Todd E; Bezner, Janet R
Abstract: Objective: Physical therapists are well positioned to meet societal needs and reduce the global burden of noncommunicable diseases through the integration of evidence-based population health, prevention, health promotion, and wellness (PHPW) activities into practice. Little guidance exists regarding the specific PHPW competencies that entry-level clinicians ought to possess. The objective of this study was to establish consensus-based entry-level PHPW competencies for graduates of US-based physical therapist education programs. Methods: In a 3-round modified Delphi study, a panel of experts (N = 37) informed the development of PHPW competencies for physical therapist professional education. The experts, including physical therapists representing diverse practice settings and geographical regions, assessed the relevance and clarity of 34 original competencies. Two criteria were used to establish consensus: a median score of 4 (very relevant) on a 5-point Likert scale, and 80% of participants perceiving the competency as very or extremely relevant. Results: Twenty-five competencies achieved final consensus in 3 broad domains: preventive services and health promotion (n = 18), foundations of population health (n = 4), and health systems and policy (n = 3). Conclusions: Adoption of the 25 accepted competencies would promote consistency across physical therapist education programs and help guide physical therapist educators as they seek to integrate PHPW content into professional curricula. Impact: This is the first study to establish consensus-based competencies in the areas of PHPW for physical therapist professional education in the United States. These competencies ought to guide educators who are considering including or expanding PHPW content in their curricula. Development of such competencies is critical as we seek to contribute to the amelioration of chronic disease and transform society to improve the human experience.